Islamic psychology in organization context: overview - Abdul Rahman, Shukran (2020)
This paper provides some exposures on the discipline of I/O Psychology; and relates it with the input on Islamic Psychology with rich local and international content. It also discusses issues faced by Muslims around the world, and link them with research and practice. The discussion requires good understanding on the concept of Psychology from Islamic Perspectives.